Arsenic Trioxide Therapy During Pregnancy: ATO and Its Metabolites in Maternal Blood and Amniotic Fluid of Acute Promyelocytic Leukemia Patients - Guo, Meihua; Lv, Jian; Chen, Xiaotong; Wu, Mengliang; Zhao, Qilei; Hai, Xin (Frontiers in Oncology, 2022)
Acute promyelocytic leukemia (APL) is extremely fatal if treatment is delayed. Management of APL in pregnancy is a challenging situation. Arsenic trioxide (ATO) is successfully applied to treat APL. ATO can be transformed into different arsenic species, which produce different toxic effects. Investigating the maternal and fetal exposure to arsenic species is critical in terms of assessing maternal and fetal outcomes, choice of optimal treatment and making decision for attempting to preserve the obstetrical and fetal well-being. In this study, maternal blood and amniotic fluid (AF) from APL patients treated with ATO in pregnancy and blood samples of non-pregnant patients were collected. Concentrations of inorganic arsenic (iAs, iAs = AsIII+AsV), MMA, and DMA were analyzed by high-performance liquid chromatography-hydride generation-atomic fluorescence spectrometry (HPLC-HG-AFS). The difference in arsenic species of plasma between pregnant patients and non-pregnant patients, distribution of arsenic compounds in AF and maternal plasma, and arsenic penetration into AF were explored. The outcomes of pregnant women treated ATO and their fetus were analyzed. No significant differences in arsenic concentration, percentage, and methylation index (PMI: primary methylation index (MMA/iAs); SMI: secondary methylation index (DMA /MMA)) between pregnant women and non-pregnant women (P > 0.05) were observed. The mean ratios of AF to maternal plasma were iAs, 2.09, DMA, 1.04, MMA, 0.49, and tAs, 0.98. Abortion rate is higher with the diagnosis at earlier gestational age, with 0%, 67%, and 100% of pregnancies ending in abortion during the third, second, and first trimester, respectively. Age of the pregnant women, the dose of ATO, and duration of fetal exposure in utero had no influences on fetal outcomes. All APL women achieved complete remission (CR). Collectively, ATO and its metabolites can easily cross the placenta. Levels and distribution of arsenic species in maternal plasma and AF gave evidence that arsenic species had different ability to penetrate the placenta into AF (iAs > DMA > MMA) and indicated a relatively high fetal exposure to ATO and its metabolites in utero. Gestational age at diagnosis was more likely to be closely related to fetal outcomes, but had no effects on the mother outcomes.